Neonatal thrombocytopenia in neonates born to the mothers with pregnancy-induced hypertension - Chaurasiya, Omshankar; Chhabra, Kawalpreet (Indian Journal of Child Health, 2019)
Introduction: Neonatal thrombocytopenia is a common clinical problem. Thrombocytopenia presenting in the first 72 h is usually secondary to placental insufficiency and caused by reduced platelet production. Objective: The objective is to evaluate the thrombocytopenia and it is associated neonatal and maternal factors in neonates born to mothers with pregnancy-induced hypertension (PIH). Methods: This study was conducted in a tertiary care hospital over a period of 1 year. Mothers with PIH were included in the study. A detailed history of the mother, physical examination, and platelet count of the newborns was done and data collected. Results: A total 111 neonates born to 106 mothers (5 pair of twin babies) with PIH were included in the study. The male-to-female ratio in these newborns was 1:1.05 with 59.4% being low birth weight (LBW), 63% term babies, and 20.72% small for gestational age babies. 59 (53.15%) neonates had thrombocytopenia and 12 with severe thrombocytopenia. Although a higher percentage of thrombocytopenia was noted with primipara, PIH symptoms at